Incarnations of material textuality : from modernism to liberature - Bazarnik, Katarzyna; Curyłło-Klag, I. (Izabela) (Cambridge Scholars Publishing, 2014)
Liberature - coined from the Latin liber - is simultaneously a movement in contemporary Polish literature, and a term referring to literary works that integrate text and material features of the book into an organic whole in accordance with the author's design. The present volume collects essays inspired by this theoretical concept, first proposed by Polish poet Zenon Fajfer in 1999, but soon picked up and elaborated on by international scholars. As noted by the contributing authors, precedin ...